Aridification, agriculture, and infant health: Evidence from soil potential evapotranspiration - Jacopo Lunghi; Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2022)
This study explores how aridity (proxied with a measure of soil potential evapotranspiration) impacts agricultural productivity and child wellbeing in Sub-Saharan Africa. Climate conditions, crop yield, and infant health measures are collected over approximately 4,000 grid cells of 0.5 x 0.5 in 34 countries. The results indicate that cells with higher soil aridity suffer from lower agricultural productivity, and infants born in arid areas are comparatively more likely to be underweight at birth and in the early years. Additionally, the aridity measure in this study captured a large share of the effect on crop yields and child health imputed to precipitations alone. The findings are applied to model projections of future climate conditions to emphasize the importance of accounting for aridity, alongside precipitations, when assessing the economic impact of climate.
Keywords: J1; J13; I15; Q54; Q56; O15; 330; Climate; aridification; agricultural productivity; potentialevapo-transpiration; child mortality; infant health; climate damages